The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1021/jp9622647
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of XPS and DFT with Reference to the Distributions of Al in Tetrahedral and Octahedral Sheets of Phyllosilicates

Abstract: Five phyllosilicate samples of dioctahedral smectite, mica, magnesium chlorite, saponite, and hectorite were studied using X-ray photoelectron spectroscopy (XPS) to determine the distribution of Al in the tetrahedral and octahedral sheets. The binding energies of the Al(2p) peaks in all the samples were obtained at 74.5 and 73.7 eV for octahedral and tetrahedral Al, respectively. The ratio of the peak areas follows the same trend as that of octahedral Al present in the phyllosilicate lattice. To confirm the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 29 publications
5
31
0
Order By: Relevance
“…From electrostatic calculations 20 it has been observed that the orientations of these hydroxyl groups are sensitive to the octahedral cation plane at the center of the clay layer. In our earlier study [21][22][23][24][25] we rationalized the structure property relationship in montmorillonite clays and observed that the hydroxyl groups expected to play a crucial role in the catalytic activity of dioctahedral clays. A recent study of Marry et al, 26 on monohydrated montmorillonite, suggested that Cs ϩ diffuse faster than Na ϩ , and the arrangement of clay surfaces play a significant part in the choice of sites occupied by cations as well in their mobility.…”
Section: Introductionmentioning
confidence: 92%
“…From electrostatic calculations 20 it has been observed that the orientations of these hydroxyl groups are sensitive to the octahedral cation plane at the center of the clay layer. In our earlier study [21][22][23][24][25] we rationalized the structure property relationship in montmorillonite clays and observed that the hydroxyl groups expected to play a crucial role in the catalytic activity of dioctahedral clays. A recent study of Marry et al, 26 on monohydrated montmorillonite, suggested that Cs ϩ diffuse faster than Na ϩ , and the arrangement of clay surfaces play a significant part in the choice of sites occupied by cations as well in their mobility.…”
Section: Introductionmentioning
confidence: 92%
“…Also, the full widths at half-maxima (FWHMs), which were in the 1.70-1.90 eV range, do not suggest the presence of several components. 33,34 Only for the pseudoboehmite oxide a larger peak width was observed, probably due to charging effects. For the anhydrous amorphous oxide an additional component was present, which is due to a minor amount of an aluminiumenriched surface oxide.…”
Section: The O/al Atomic Ratio Of the Oxide Layers Determined From Phmentioning
confidence: 98%
“…Anderson and Swartz (1974) reported identical A1 2p binding energies for tetrahedral and octahedral aluminum in aluminosilicates. Ebina et al (1997) and Barr et al (1997) observed that the Al 2p binding energy increased with an increase in the ratio of octahedral to tetrahedral Al. Barr et al (1997) noted that a more positive octahedral sheet character coupled with the relatively net negative tetrahedral sheet results in ionic AlÀO bonds that are stronger in kaolinite and allophane than in Al 2 O 3 .…”
Section: Tetrahedral Sheet: Silicon and Aluminummentioning
confidence: 99%